2019
DOI: 10.17573/cepar.2019.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Reform from the Post-New Public Management Perspective: Review and Bibliometric Analysis

Abstract: The aim of this article is to evaluate the impact of public sector reform on academic literature from the post-NPM perspective. There have been several investigations into post-NPM public governance models and their impact on public sector reform. Yet, the research problem faced when analysing post-NPM literature is the lack of studies examining the multitude of possible public governance models (PGM) with sufficient comprehensiveness, especially in Central and Eastern European (CEE) states. In order to effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Our results show the characteristics of at least five different public governance models characteristics are present in Slovenian public administration, where the basis of the state administration institutions are the practices of the Neo-Weberian model. Given that today several of its elements remain indispensable, like the hierarchy, professionalism, and political neutrality of the public administration operating according to legislation (Pollitt and Bouckaert 2011;Bauer and Trondal 2015;Ropret and Aristovnik 2019), followed by the practices of New Public Management, Good Governance and Hybrid models. Iacovino et al (2017) found similar results in their case study of the Tuscany Region where traditional public administration, New Public Management and public governance backgrounds coexist in the same context and at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show the characteristics of at least five different public governance models characteristics are present in Slovenian public administration, where the basis of the state administration institutions are the practices of the Neo-Weberian model. Given that today several of its elements remain indispensable, like the hierarchy, professionalism, and political neutrality of the public administration operating according to legislation (Pollitt and Bouckaert 2011;Bauer and Trondal 2015;Ropret and Aristovnik 2019), followed by the practices of New Public Management, Good Governance and Hybrid models. Iacovino et al (2017) found similar results in their case study of the Tuscany Region where traditional public administration, New Public Management and public governance backgrounds coexist in the same context and at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…(Weber 1946;Wojciech 2017;Dunleavy and Margetts 2015). Even though this model is already around 100 years old, some elements remain essential today, such as hierarchy, professionalism, and the political neutrality of the public administration that operates according to legislation (Pollitt and Bouckaert 2011;Bauer and Trondal 2015;Ropret and Aristovnik 2019;Kukovič and Justinek 2020). However, theory and practice had created deviations that questioned the credibility of traditional bureaucracies.…”
Section: Overview Of Public Governance Modelsmentioning
confidence: 99%
“…To understand the evolution of academic contributions to the topic of participatory budgeting, we employed the combined research approach of Ropret and Aristovnik (2019), Agrifoglio et al (2020), andSpasenić et al (2022). The first phase refers to the identification of all relevant papers within the Web of Science database (WoS).…”
Section: Methodsmentioning
confidence: 99%
“…The good governance model emerged as an upgrade of the bureaucratic (Weberian) governance model and the later New Public Management model, both including different variations (Agere 2000;Bevir 2011;Bevir et al 2003;Edgar et al 2006;Graham et al 2003;Kovač et al 2016;Rao 2013;Ropret and Aristovnik 2019;Smith 2007). The most significant advantage of the Weberian model was its ability to solve quite structured problems based on regulation and economies of scale.…”
Section: Good Governance In the Covid-19 Crisismentioning
confidence: 99%